A survey for Batrachochytrium salamandrivorans in Chinese amphibians. Issue 6 (1st December 2014) - Zhu, Wei; Xu, Feng; Bai, Changming; Liu, Xuan; Wang, Supen; Gao, Xu; Yan, Shaofei; Li, Xianping; Liu, Zetian; Li, Yiming
Abstract: For the last decade, chytridiomycosis was considered to be caused by a single species of fungus, Batrachochytrium dendrobatidis ( Bd ), but a second chytrid species, Batrachochytrium salamandrivorans ( Bs ), was recently isolated from an infected Salamandra salamandra in the Netherlands. To date, Bs has only been found in the Netherlands. To assess whether Bs is present in China, we analyzed a total of 665 samples, including 425 wild samples, 41 preserved specimens, and 199 captive samples, from 30 different species, including both urodeles and anurans. Our sample sites covered 15 provinces in China. All of the samples tested negative for Bs, resulting in a 95% confidence limit for a prevalence of 0.6%. The absence of Bs observed in this large-scale survey in China has significant implications for amphibian conservation and for border trade management strategies intended to control amphibian diseases. We strongly recommend the continued close monitoring of Bs to verify the status of this potentially devastating amphibian fungus in China.